Algorithm to List All Possibilities of Minimizing The Number of BSO’s of Matrix Converters - Igney, Jens; Hahn, Ingo (2024 Energy Conversion Congress & Expo Europe (ECCE Europe), 2024)
As with other self-commutated inverters, the matrix converter offers the option of discontinuous modulation. This paper presents an algorithm that lists all duty cycle matrices that allow pulse patterns with only six instead of twelve branch switching operations (BSO’s) per modulation period. It further provides a classification scheme for such duty cycle matrices. The algorithm can be used as a first step within improved modulation strategies with reduced number of branch switching operation
Keywords: AC-AC power conversion; matrix converters; pulse width modulation; branch switching operation (BSO); discontinuous modulation; classification scheme

A new matrix converter modulation strategy maximizing the control range - Igney, Jens; et al. (2004)
This paper presents a new modulation strategy for matrix converters, which provides the maximum control range including reactive input power. The modulation strategy bases on modern representations of the switch state in the space vector domain. There, geometrical considerations lead to a comprehensible strategy to eliminate free variables without reducing the intrinsic control range of the switch matrix. A comparison with other modulation strategies shows, that this control range exceeds the control range of all previously proposed modulation strategies. A further advantage is, that low switching losses are expected, because a maximum of switches are idle during a modulation period.

Control Algorithms for Matrix Converters With Low Mathematical Complexity - Igney, Jens; Hahn, Ingo (21st International Symposium on Power Electronics (Ee), 2021)
Due to the degrees of freedom inherent in matrix converter modulation, there are a large number of different, seemingly contradictory modulation strategies. This work contributes to a systematization of at least a subset of the strategies. For this purpose, a systematic derivation of direct control algorithms is performed. "Direct" is meant in the sense that the duty cycles are computed using only basic arithmetic. Since such algorithms do not invoke mathematical library functions, they can be easily implemented in embedded processors or programmable logic.Due to their direct computability and systematic derivation from theory, the algorithms can be regarded as archetypes of matrix converter modulation and can be a valuable aid in comparing different control algorithms.
Keywords: Systematics; Program processors; Modulation; Power electronics; Libraries; Complexity theory; Classification algorithms; Matrix converters; Algorithm; Classification

Implementation of a matrix converter space vector control in programmable logic - Igney, Jens; et al. (Epe Journal, 2002)
To control a matrix converter different modulations are possible. To benefit from the new topology the rectifying and inverting vector modulation (RIVM) can be used. It is a complex theory but this article presents a realization in one single programmable logic device. Additionally pulse pattern execution (PWM, commutation strategies and input voltage/current filtering) are situated in the same device. This was possible after the optimization and the reduction of the necessary calculation steps. This new solution works without an extra micro-controller or a digital signal processor (DSP). It allows great reduction in costs of matrix converter controls implementation and increases the performanc

Matrix converter commutation strategies with and without explicit input voltage sign measurement - Igney, Jens; Braun, Michael; et al. (IEEE Transactions on Industrial Electronics, 2002)
This paper gives an overview to voltage-controlled matrix converter commutation. Conventional converter systems with explicit sign measurement circuits that were necessary for the commutation in the past are discussed. New operation methods eliminating these extra measuring circuits are presented. The paper explains the new methods. Advantages and disadvantages of different approaches are discussed. The robustness of the new methods against disturbance is proved and measurements on a 5.5-kW matrix converter system are show
Keywords: Bidirectional switch; Commutation; Critical area; Matrix converter; Prevention; Prohibition; Replacement; Sign evaluation; Sign measurement

Matrixumrichter zur Speisung eines feldorientiert geregelten Asynchronmaschinenantriebs Innovationen in Aufbau und Steuerung des Matrixumrichters - Igney, Jens; Braun, Michael (VDI-Berichte 1963, 2006)
Das Hauptmerkmal des Matrixumrichters ist die direkte Energiewandlung ohne Energiespeicher im Zwischenkreis. Daraus ergeben sich Vorteile in Bezug auf den Platzbedarf, Wirkungsgrad und die Leistungsdichte des Umrichters. Der Preis dafür ist ein höherer Aufwand an Halbleitern und deren Ansteuerung. Durch den Preisverfall der Leistungshalbleiter und die Steigerung der Leistungsfähigkeit der Signalverarbeitung fällt dieser Nachteil immer weniger ins Gewicht. Am Elektrotechnischen Institut werden schon seit längerer Zeit Forschungsarbeiten an Direktumrichtern, speziell an Matrixumrichtern durchgeführt. Dieser Beitrag stellt die jüngsten Forschungsergebnisse vor, die den Aufbau von Matrixumrichtern vereinfachen und seine Fähigkeiten erweitern. Die sichere Kommutierung ersetzt das messtechnische Problem der Vorzeichenerfassung durch einen kleinen Mehraufwand in der Signalverarbeitung. Der Umrichterschutz mit Varistoren und Suppressordioden fällt platzsparender aus, als Clampschaltungen mit Kondensator. Es wird gezeigt, dass sich die Signalverarbeitung des Matrixumrichters ohne kostspielige Prozessoren bewerkstelligen läßt. Ein neuer Steueralgorithmus ermöglicht Betriebspunkte mit hoher Blindleistung am Eingang, die von den bisher vorgestellten Verfahren nicht erreicht werden können. Anhand eines Reversiervorgangs einer matrixumrichtergespeisten Asynchronmachine wird die Umsetzung der gezeigten Schaltungen und Verfahren in der Praxis demonstriert. Die vorgestellten Neuerungen etablieren den Matrixumrichter in den genannten Anwendungsgebieten als vielversprechende Alternative zum Zwischenkreisumrichter. Direct energy conversion without energy storage in a dc-link is the characteristic feature of the matrix converter. Consequential benefits are low space requirement, good efficiency and high power density. The prize to be paid is higher complexity with a view to the amount of semiconductors and their control. This disadvantage gets more and more irrelevant because of continuous reduction of semiconductor prizes and increasing performance of signal processing devices. The Elektrotechnisches Insitut of the Universität Karlsruhe (TH) has been engaged in research on direct convertes, especially matrix converters, for several years. This paper describes an overview over effective problem solutions and their application in a field orientated induction motor drive fed by a matrix converter which has been constructed and examined at the Elektrotechnisches Institu

Modulation Strategy and Control Range Function for Matrix Converters Without Trigonometric Functions - Igney, Jens; Hahn, Ingo (2022 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2022, 2022)
The theory presented in this paper preserves the inherent symmetry of the matrix converter. In this way, analytically simple and computationally inexpensive formulas are derived to describe the control range and modulation of the classic 3×3 matrix converter. No trigonometric formulas need to be evaluated to verify the control range and to calculate the modulation. This is beneficial for the realization of efficient real-time program code.
CRIS-Team Scopus Importer:2022-09-02
Keywords: algorithm; control limits; control range; matrix converter; modulation strategy

Space vector modulation strategy for conventional and indirect matrix converters - Igney, Jens; Braun, Michael (2005 European Conference on Power Electronics and Applications, 2005)
This paper presents a modulation strategy for conventional matrix converters (CMC) and indirect matrix converters (IMC). The benefit of the strategy are the clarity of the space vector approach, the simplicity of the signal processing and a wide and analytically calculable control range. The control range nearly reaches the theoretical maximum of the C
Keywords: Modulation strategy; Matrix converter; Vector control